Ethnobotanical Survey of Important Wild Medicinal Plants of Tehsil Gojra, District Toba Tek Singh, Punjab, Pakistan - Tufail, Muhammad; Hussain, Khalid; Nawaz, Khalid; Bhatti, Khizar Hayat; Yasin, Ghulam; Ali, Syed Saqib (Ethnobotany Research and Applications, 2020)
Abstract Background: Almost every region of the world is stacked with a large number of medicinal plants. Medicinal plants are the major source to cure many diseases among the peoples of the world. There are still many areas in the world which have not been explored for its flora. Pakistan is also a rich with variety of flora but still there are some areas which need to be studied. This study was conducted to enlist the wild ethnomedicinally important plant species and traditional medicinal knowledge of Gojra, district Toba Tek Singh, Punjab, Pakistan. Methods: Field surveys were arranged to enlist the important medicinal plants and traditional knowledge from the local community through questionnaire and group discussion during 2019-2020. Data collected through questionnaire was consist of plant local name, medicinal use, method of use and part used. Results: There were more than 100 plant species including cultivated and wild but only 47 wild plants species were ethnomedicinally important as reported by local respondents that were placed in 20 families. It was noted that leaves had highest percentage (54%) of its use in various prescriptions. Acacia modesta Wall. (Fabaceae) was the most common tree used in teeth pain and gastritis with 0.73 UV (Use Value) and 0.075 RFC (Relative Frequency of Citation) values. Achyranthes aspera L. (Amaranthaceae) showed 0.85 UV and 0.088 RFC values and was used to cure fever, asthma and cough. For stomach, gastric and urinary disorders, Chenopodium album L. (Amaranthaceae) was used with 0.78 UV and 0.156 RFC values. Cichorium intybus L. (Asteraceae) has much importance in summer season as it is commonly used to reduce thirst in hot weather conditions. Its UV was 0.74 and RFC was 0.132. Leaves, fruits and barks of Dalbergia sissoo DC. (Fabaceae) was used to control nosebleed, gonorrhoea, stop vomiting and skin disorder. It has 0.72 UV and 0.075 RFC values. Eucalyptus globulus Labill. (Myrtaceae) was used to treat common cold, respiratory infections and asthma. Its leaves were used to provide steam to the asthma patients. It showed 0.76 UV and 0.08 RFC values. Ricinus communis L. (Euphorbiaceae) was a common weed in the area with 0.74 UV and 0.19 RFC values. Its seeds and leaves were useful to treat rheumatic pain, joint pain and constipation. Acacia modesta showed the highest Fidelity Level (FL) value that was 87% and used in teeth and gastric problems. Conclusions: It was concluded that there are many useful wild plants in Tehsil Gojra, district Toba Tek Singh, Punjab, Pakistan that are used in traditional medicines to cure many diseases. These plants also showed pharmacological importance that can be utilized to develop medicines. Keywords: Gojra, ethnobotany, flora, survey